Comparative Study on Quality of Bamboo Seedlings in Root Trainers and Polythene Bags - Gera, Mohit; Koul, Ajay Raj; Gera, Neelu (Indian Forester, 2007)
Comparative study on quality of Bamboo seedlings of two species, viz., Dendrocalamus strictus and Bambusa bambos raised in different sized root trainers, polythene bags kept of mounted angle iron (MAI) beds and nursery beds has shown that significant variations exist in almost all seedling morphological parameters, viz., height, collar diameter, number of tillers, shoot biomass, fibrous root biomass, rhizome biomass and total root biomass among all the treatments. When compared on the basis of seedling quality parameters, viz, sturdiness, root/shoot ratio, ratio of fibrous to total root biomass and rhizome to total root biomass, the seedlings raised in 300 cc root trainers and polythene bags kept on MAI beds performed better. The study has shown that good quality Bamboo seedlings can be raised in root trainers on large scale. The limited space available to the plant in root trainers had no adverse effect on rhizome development. The system also facilitates mass propagation of Bamboo stock through macroproliferation.